The Importance Of Tax Benefits And Preferences In Measuring The Negative Effects Of The Coronavirus Pandemia And Global Crisis On The Economic Sectors - RAMAZANOVNA, KUZIEVA NARGIZA (The journal of contemporary issues in business and government, 2021)
The article analyzes the mechanism of the effective application of tax and customs benefits while mitigating the negative impact of the coronavirus pandemic and global crisis on the economy, social support of the population, stimulation of economic sectors and business entities.